Character Education Strategies for Children with Special Needs - Steven S. N. Rogahang (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Character education aims to teach children to develop good behaviour patterns and character traits from an early age so that these positive traits become an inherent and rooted part of them. Children with special needs have abnormalities or differences in physical, mental, and social compared to normal children. The type of research used is literature or literature studies, where researchers rely on various literature sources to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. Strategies that can be used to recognize the character of children with special needs include opening a more open mind, adapting to children, increasing emotional closeness with children, teaching children to develop skills, learning children's habits and needs, and involving children in available therapies. Services to children with special needs cannot be equated but must be tailored to the characteristics of their individual needs and abilities.